Effects of Heavy Metals on the Performance and Mechanism of Anaerobic Ammonium Oxidation for Treating Wastewater - Ren, Qiang; Gao, Junling; Wang, Chenfeng (Frontiers in Chemical Engineering, 2022)
Persistence of ammonium nitrogen and heavy metals in wastewater still remains a challenge, and many wastewater treatment plants face the challenge of removing nitrogen under the heavy metals stresses. There is no preferred method for the biological treatment of the wastewater containing nitrogen and heavy metals with the possible exception of the anaerobic ammonium oxidation (Anammox), since it has shown promise for removing nitrogen under the heavy metals stresses. This paper reviews the recent research results of nitrogen removal performance and mechanism by Anammox process under heavy metals stresses, mainly discussing the enhancing and inhibition effects of heavy metals on performance of Anammox reactor. The influencing mechanism of heavy metals on the microbial community and EPS (extracellular polymeric substances) are also presented and examples are given for explanation. The main problems of present researches are pointed out and it is proposed that unifying the metal ions concentrations of inhibiting or promoting Anammox activity are necessary for the development and industrial of Anammox process. The information of this review can offer a great possibility for achieving desired nitrogen removal in the wastewater treatment under heavy metals stresses and with significant energy savings.